Building a valuable professional development course: instructor effort vs. perceived student value of activities in an online biotechnology course - Chen, Stefanie H.; Dums, Jacob T.; Hasley, Andrew O. (Frontiers in Education, 2024)
Providing undergraduate and graduate students with the appropriate preparation for transitioning to careers in their field after graduation is a key goal of higher education institutions, with many programs employing professional development workshops or courses to assist students and provide hands-on skills in this area. Although a wide variety of activities could benefit students, instructor and career specialist time is limited. Here, we describe an online biotechnology professional development course for undergraduate and graduate students, covering career exploration and the job search process, and the students’ perceptions of the activities offered based on survey data. Overall response to the course was positive, with students at various stages of their education indicating appreciation of most of the course assignments. Interestingly, students ranked the activities that took the most instructor time, namely review of application materials, mock interviews, and career panels, as the most valuable for their personal development. The career exploration aspects of the course influenced students to be open to new possibilities. However, students struggled to make time to complete the assignments for a fully online, largely asynchronous course. Discussion of the value of the course activities, their relevance to social cognitive career theory and cognitive information processing, and suggestions for smooth implementation are provided.